2010
DOI: 10.1111/j.1460-9568.2010.07344.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning rules and persistence of dendritic spines

Abstract: Structural plasticity of dendritic spines underlies learning, memory and cognition in the cerebral cortex. We here summarize fifteen rules of spine structural plasticity, or 'spine learning rules.' Together, they suggest how the spontaneous generation, selection and strengthening (SGSS) of spines represents the physical basis for learning and memory. This SGSS mechanism is consistent with Hebb's learning rule but suggests new relations between synaptic plasticity and memory. We describe the cellular and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 127 publications
8
77
0
1
Order By: Relevance
“…Previous studies have shown that there are structural correlates of synaptic plasticity (Kasai et al, 2010a(Kasai et al, , 2010b. In general, spine size is correlated with the strength of synapses (Kasai et al, 2010a(Kasai et al, , 2010b. Thus, the enlargement of dendritic spines in IT-type neurons of the PD and LID models suggests that there are associated changes in the electrophysiological properties of these neurons.…”
Section: Morphological Changes In Dendritic Spines Of It-type Neuronsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have shown that there are structural correlates of synaptic plasticity (Kasai et al, 2010a(Kasai et al, , 2010b. In general, spine size is correlated with the strength of synapses (Kasai et al, 2010a(Kasai et al, , 2010b. Thus, the enlargement of dendritic spines in IT-type neurons of the PD and LID models suggests that there are associated changes in the electrophysiological properties of these neurons.…”
Section: Morphological Changes In Dendritic Spines Of It-type Neuronsmentioning
confidence: 94%
“…The size of dendritic spines in the LID was larger than those in the levodopa-treated control. Previous studies have shown that there are structural correlates of synaptic plasticity (Kasai et al, 2010a(Kasai et al, , 2010b. In general, spine size is correlated with the strength of synapses (Kasai et al, 2010a(Kasai et al, , 2010b.…”
Section: Morphological Changes In Dendritic Spines Of It-type Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable feature of excitatory and inhibitory synapses is their high level of structural variability 2 and the fact that their morphologies and stabilities change over time 3 . This phenomenon is regulated by activity, and the size of spine heads correlates with synaptic strength 4 , presynaptic properties 5 and the long-term stability of the synapse 6 .…”
Section: Molecular Mechanisms Of Synapse Remodellingmentioning
confidence: 99%
“…Notably, because recent work suggests (24,25) a potential relationship between spine shape, synaptic function, and morphological rearrangements of the spines as forms of developmental or experience-dependent plasticity (26), we performed patch-clamp experiments in Nacc shell slices obtained from ethanol-withdrawn rats to evaluate whether long-term depression (LTD) formation and its underlying synaptic currents are modified by experimental conditions.…”
mentioning
confidence: 99%